Occurrence and characterization of pearls from oysters of the genus Crassostrea. (4th April 2016) - Batista, Frederico M.; Grade, Ana; Power, Deborah M.; Ruano, Francisco; Harper, Elizabeth M.
Abstract : The occurrence of pearls in the 'true' oysters, the Ostreioidea, is poorly documented despite being the most produced mollusc species in the world. Oysters of the Crassostrea genus were collected in two different sites in southern Portugal where both Crassostrea angulata and C. gigas are present, namely in: (1) the Ria Formosa lagoon where pearls were not observed (N = 446); and (2) the Guadiana estuary where pearls were found in 12 out of the 798 oysters analysed. The pearls were located mainly at the edge of the right mantle lobe in the inhalant chamber and their maximum length ranged from 0.9 to 5.5 mm. Almost all the pearls had a white-cream colouration with the exception of two pearls that had a black-brown colour. X-ray diffraction analysis of one pearl showed that it was entirely calcitic with no traces of either aragonite or vaterite. The pearls observed were therefore non-nacreous pearls. Scanning electron microscopy (SEM) revealed a diversity of microstructures including prismatic, foliae-like sheets and blocky textures, i.e. highly reminiscent of the host oyster shell microstructures. Parasites (e.g. parasitic copepods, Haplosporidium -like plasmodia) and signs of diseases (e.g. foot disease) were observed in some of the oysters analysed, but they were not associated with the occurrence of pearls. The present work is one of the few studies on the occurrence of natural pearls in 'true' oysters and to our knowledge the first description of their microstructure by SEM.